The Role of Trust and Moral Obligation in Beef Cattle Feed-lot Veterinarians’ Contingent Adoption of Antibiotic Metaphylaxis Recommendations - R. Dean, Wesley; Alex McIntosh, William; Scott, H. Morgan; S. Barling, Kerry (The International Journal of Sociology of Agriculture and Food, 2011)
In light of concern over possible public health consequences arising from the use of antibiotics in the animal industries, we examine the willingness of beef-cattle feed-lot veterinarians to forgo the recommendation of antibiotic mass treatment to their beef-feed-lot clients as a contingency based on the demonstration of a definite harm to human health. We explore this contingency as an example of the negotiation by health professionals of conflicting obligations to public health, animal well-being, and the economic pressures of feed-lot medicine. We base our study on survey data (n=103) collected from a national sample of U.S. feed-lot veterinary practitioners. Factors that predict willingness are primarily psycho-social, including social influence, moral duty, and trust or distrust, characterized as competency. We define the dimensions of trust across an array of salient others determined by the structural and regulatory context of the American cattle feeding industry.